Antibiotic management guidelines need to be updated - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
According to an analysis published in the authoritative medical journal "BMJ" the duration of stadard antibiotic treatment should be substantly reduced, since it does not affect either the effectiveness or the antibiotic resistance.